CO2 Reduction: Beyond d Orbits: Steering the Selectivity of Electrochemical CO2 Reduction via Hybridized sp Band of Sulfur‐Incorporated Porous Cd Architectures with Dual Collaborative Sites (Adv. Energy Mater. 45/2020). Issue 45 (1st December 2020) - Wu, Yunzhen; Zhai, Panlong; Cao, Shuyan; Li, Zhuwei; Zhang, Bo; Zhang, Yanting; Nie, Xiaowa; Sun, Licheng; Hou, Jungang
Abstract : In article number 2002499, Jungang Hou and co‐workers report a sulfur‐incorporated porous Cd architecture with superior activity for selective CO generation. The linear scaling relations are naturally eliminated, enabling the convenient modulation of selectivity for CO2 reduction toward CO rather than HCOOH. The covalently hybridized sp band system with dual collaborative sites is vividly visualized by the inseparable king bird in this picture.